A "Capital of Hope and Disappointments": North African Families in Marseille Shantytowns and Social Housing. Issue 1 (1st March 2022) - Harris, Dustin Alan
Abstract: This article traces the history of specialized social housing for North African families living in shantytowns in Marseille from the early 1950s to the mid-1970s. During the Algerian War, social housing assistance formed part of a welfare network that exclusively sought to "integrate" Algerian migrants into French society. Through shantytown clearance and rehousing initiatives, government officials and social service providers encouraged shantytown-dwelling Algerian families to adopt the customs of France's majority White population. Following the Algerian War, France moved away from delivering Algerian-focused welfare and instead developed an expanded immigrant welfare network. Despite this shift, some officials and social service providers remained fixated on the presence and ethno-racial differences of Algerians and other North Africans in Marseille's shantytowns. Into the mid-1970s, this fixation shaped local social assistance and produced discord between the promise and implementation of specialized social housing that hindered shantytown-dwelling North African families' incorporation into French society.